ZEOLIT ALAM SEBAGAI FILLER PADA CAMPURAN LASTON (AC) DENGAN ASPAL PEN 60/70 DAN ASBUTON (BNA) BLEND 75:25 - Suparma, Latif Budi; Purnomo, Wahyu; Andrian, Muhammad; Saleh, Alfian (FSTPT Indonesia, 2015)
General use asphalt mixture in Indonesia is Asphalt Pen 60/70 and rarely utilized Buton Natural Asphalt Blend 75:25. In Indonesia, natural zeolite cannot be utilized optimally as pavement and lower prices of stone dust. The purpose of this study was to determine, looking for the best mixture using zeolite. Testing was conducted by Marshall Method. In this study, variation of natural zeolite in the mixture used 25%, 50%, 75% and 100%. Marshall test results (stability) mixtures using zeolite has a value above which use a mixture of stone dust. The ability to resist deformation in the mix by using natural zeolite has a better value than a mixture of stone dust. Based on the test can be concluded that the natural zeolite can be used as a substitute for the stone dust filler in the mix pavement Asphalt Concrete (AC), with the percentage of natural zeolite optimally between 25% at Pen bitumen 60/70 and 50% at BNA Blend 75:25. Asphalt Concrete (AC) mixture by using natural zeolite has a value of weight-bearing (stability), durability, and flexibility is better than mix with stone dust.